Adaptation to endurance training - Wackerhage, H. (Genetics and molecular biology of muscle adaptation, 2006)
CHAPTER CONTENTS Learning Objectives 165 Introduction 166 Practical Endurance Training 167 Long Slow Distance 167 Medium and High-Intensity Continuous Training 168 IntervaI and Fartlek Training 168 What Determines the Overall Training Load? 168 Fibre Phenotypes and Phenotype Conversions 169 Regulation of Phenotype Conversions 169 Location and Regulation of MHC Isoform Genes 175 Signal Transduction During Exercise 176 ACTN3 Polymorphism 177 Metabolic Enzymes and Mitochondria in Endurance Training 178 Adaptation of Oxidative Enzymes 179 Adaptation of Fat Metabolism 180 Regulation of Mitochondrial Biogenesis 180 Mitochondrial Biogenesis and Endurance Exercise 181 Endurance Exercise-Induced Angiogenesis 185 Dp-regulation of Angiogenic GrowthFactors 186 Dp-regulation of Capillary Formationand Maturation 188 The Complete Picture 189 Development of the Athlete'sHeart 190 Key Points 191 References 192